EFISIENSI PENGGUNAAN WAKTU PENGISIAN BAHAN BAKAR ALAT BERAT PADA PT.PAMAPERSADA NUSANTARA DISTRIK BAYA KUTAI KARTANEGARA - Mustopa, Ari (EKONOMIA, 2013)
Efficient Use of Fuel Filling Time At PT. Pamapersada Baya district in village location Buana Tenggarong Seberang Jaya subdistrict, Kutai regency, East Kalimamtan under the guidance of Mrs. Elfreda A. Lau and Mr Adi Suroso.PT. Pamapersada is open cast mining contracting company which is engaged in coal mining, and has many locations and work areas are scattered throughout the Indonesian, one of which is a district located in the village aged Buana Jaya, Seberang Tenggarong district, Kutai regency, East Kalimantan Province. In the production of PT. Pamapersada using heavy equipment, which includes equipment loaders and excavators as damp as a tool hauler truck .Main problems of writing this research is: What level of usage time refueling machine at PT. Pamapersada Baya district has efficient ? Objective: To determine whether or not the system is efficient fueling of heavy equipment and the level of delay time and lost time that occurred during refueling took place at PT. Pamapersada Baya district, Kutai regency.Hypothesis: The use of queuing systems with Configuration Model Single Channel Multi Phase (Single Phase Multi Cannel) by PT. Pamapersada very appropriate because it will yield accurate information about the lost time that occurs during refueling.Kofigurasi System Single Channel Multi Phase (Single Phase Multi Cannel) a time efficient approach lost time during refueling queue. With queuing theory Configuring Single Channel Multi Phase (Single Phase Multi Cannel) obtained results: 1) the level of busyness system Ï = 0.7894 hours or 47.367 minutes to complete 30 units of heavy equipment that has 2 outlet refueling. 2) In one hour there is a system busy time spare minute 12.633 or 13.23 %. So based on the data for normal refueling 3.16 minutes, still save time of 1.59 minutes.Can be concluded: 1) The application of queuing theory calculations Configuration Single Channel Multi Phase (Single Phase Multi Cannel) is very effective. 2) From the results of the study and after calculation, that the hypothesis is accepted and efficient because the value of Ï is 1.57 minutes for the one-time refueling of heavy equipment.